Bidirectional motion observed in the compact symmetric object 1946+708. - Taylor, G B (1995)
We present the first direct measurements of bidirectional motions in an extragalactic radio jet. The radio source 1946+708 is a compact symmetric object with striking S-symmetry identified with a galaxy at a redshift of 0.101. From observations 2 years apart we have determined the velocities of four compact components in the jet, the fastest of which has an apparent velocity of 1.09 h-1c. By pairing up the components, assuming they were simultaneously ejected in opposite directions, we derive a 1 lower limit on the Hubble constant, H0 > 42 km.s-1.Mpc-1.